ANALYSIS OF THE PATTERN AND MECHANISM OF ELBOW INJURIES RELATED TO ARMBAR-TYPE ARMLOCKS IN JIU-JITSU FIGHTERS - ALMEIDA, THIAGO BERNARDO CARVALHO DE (Acta Ortop Bras, 2017)
OBJECTIVE: The objective of this study was to analyze elbow injuries and their probable mechanism in Jiu-Jitsu fighters resulting from the armbar-type armlock. METHODS: We evaluated 5 high-performance Jiu-Jitsu fighters from the Gracie Elite gym who were injured during a tournament. All were healthy males with a mean age of 28.8 years. The right arm was involved in three patients (60%). The athletes were followed for approximately 4.6 months, and pain was present in all cases. Clinical examination of the elbow was performed immediately after the injury and when magnetic resonance imaging (MRI) was performed. The radiography showed no changes. Clinical examination detected specific tender points on the medial and anterior topography of the elbows, but no ligamentous instability of the elbow was seen during dynamic testing. RESULTS: The main MRI findings were injury to the common flexor tendon and the ulnar collateral ligament, bone contusion of the distal humerus and olecranon, and joint effusion. CONCLUSION: The main pattern of injury indicated by the MRI in the athletes was injury to the medial elbow complex. The primary mechanism that determined the injury was most likely elbow hyperextension applied with the forearm in neutral position of forearm. Level of Evidence IV, Case Series.